The Effect of Pop-Up Book Teaching Media on Students’ Learning Interest in Science: Evidence from Junior High School in Indonesia - Andriani Utami; Salamah Salamah; Elvida Sari Yunilarosi (Yayasan Darussalam Bengkulu, 2023)
This study examines whether pop-up book teaching media are associated with students’ learning interest in science, focusing on the human respiratory system topic. A quantitative correlational design was employed with a purposive sample of 21 eighth-grade students (class VIII-A) from SMP Negeri 21 Bengkulu Selatan, Indonesia. Learning interest and perceptions of the pop-up book were measured using validated Likert-type questionnaires totaling 32 items (16 items per construct). Data were analyzed using Pearson’s product–moment correlation and a follow-up significance test. Results showed a strong positive association between the use of pop-up book media and students’ learning interest (r = 0.781, p < 0.05), confirmed by a significant t-value (t(19) = 5.446 > t_table = 2.093). These findings indicate that innovative three-dimensional, interactive print media can meaningfully enhance students’ engagement with science content that is typically abstract at the lower-secondary level. The study contributes empirical evidence from an Indonesian junior-high context and offers practical implications for teachers to adopt visually rich, hands-on instructional tools to stimulate learning interest.